2022
DOI: 10.3390/ma15207071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Etching Times with Hydrofluoric Acid on the Bond Strength of CAD/CAM Ceramic Material

Abstract: The objective of this study was to evaluate the influence of hydrofluoric acid (HF) and conditioning time on the micro-shear bond strength (µSBS) between dual-cure resin cement and glass-ceramic materials, such as lithium disilicate ceramic (IPS e.max CAD, Ivoclar Vivadent) (EX) and leucite-reinforced ceramic (IPS Empress CAD, Ivoclar Vivadent) (EP), and also a hybrid ceramic (Vita Enamic, Vita Zahnfabrik) (VE). Eighteen sections with 1 mm thickness were cut from each CAD/CAM material and randomly divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In addition, a previous study mentioned that treating EMAX with HF for 20 s according to the manufacturer's instructions increased surface energy and reduced contact angle for adhesives, providing ideal microporosities for mechanical interlocking 42 . For standardization purposes, in the present study EMAX was etched for 60 s since it was reported that this duration provides the highest bond strength for EMAX and VM, 25 and several studies revealed that the etching time whether it is 20,30,40,60, 90, or 120 s do not have a significant effect on the μSBS values obtained for EMAX 24,26 . Despite the difference in etching time, similarly, HF + SA application on EMAX enhanced μSBS significantly and increased the percentage of mixed and cohesive failure types in the present study.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In addition, a previous study mentioned that treating EMAX with HF for 20 s according to the manufacturer's instructions increased surface energy and reduced contact angle for adhesives, providing ideal microporosities for mechanical interlocking 42 . For standardization purposes, in the present study EMAX was etched for 60 s since it was reported that this duration provides the highest bond strength for EMAX and VM, 25 and several studies revealed that the etching time whether it is 20,30,40,60, 90, or 120 s do not have a significant effect on the μSBS values obtained for EMAX 24,26 . Despite the difference in etching time, similarly, HF + SA application on EMAX enhanced μSBS significantly and increased the percentage of mixed and cohesive failure types in the present study.…”
Section: Discussionmentioning
confidence: 82%
“…After the aging protocol, specimens were randomly separated into four main groups as follows: Control: no treatment was applied on the specimen surface. AL: Specimen surfaces were sandblasted from 10 mm above, with a sandblaster (Airsonic, mini sandblaster; Hager Werken) at a pressure of 1.5 bar using aluminum oxide powder (Cobra; 50 μm Al 2 O 3 , Renfert GmbH, Hilzingen, Germany). And they were rinsed with distilled water for 30 s and dried with oil‐free air to clean the residues. HF: The specimen surfaces were etched with 9% hydrofluoric acid (Ultradent) for 60 s 24–26,41 and then were rinsed and air‐dried with an oil‐free air/water syringe. MEP: Monobond Etch and Prime was applied gently with a micro brush and rubbed for 20 s. After waiting for 40 s, it was washed off and air‐dried for 10 s. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Avram et al 24 found that machinable e max CAD ceramic achieved superior results when etched with 9.5% HF acid for 60s. Moreover, no significant differences were found between the bond values of etching time (30 s and 60 s) which led to the fact that; for lithium disilicate ceramic bonding, it is possible to use either a higher concentration HF acid with the recommended manufacturer' time or a higher etching time with the acid concentration recommended by manufacturer.…”
Section: Discussionmentioning
confidence: 99%